Relationship between different domains of physical activity and positive mental health among young adult men - Appelqvist-Schmidlechner, Kaija (BMC Public Health, 2020)
BACKGROUND: There is growing evidence on positive effects of physical activity (PA) on mental health. However, the focus of previous research on this relationship has typically been on mental health from the perspective of mental health problems rather than from the perspective of mental wellbeing. Further, previous research has commonly focused rather on leisure time PA without evidence on the role of other domains of PA. The aim of the present cross-sectional study was to investigate the relationship between positive mental health (PMH) and different domains of PA in young Finnish men. The secondary aim was to examine the reasons for physical inactivity among individuals with a low level of PMH. METHODS: Positive mental health (measured with Short Warwick-Edinburgh Mental Wellbeing Scale, SWEMWBS), self-reported leisure time, occupational and commuting PA as well as reasons for physical inactivity were measured using questionnaires (n = 456, mean age 29 years) among young Finnish males. Logistic regression modelling was used to generate odds for low and high levels of positive mental health for different levels of PA and sociodemographic variables. RESULTS: A weak positive association between leisure time PA and PMH was found in men with a low level of PMH (OR = 0.33, 95% CI 0.13–0.86). No association was found in the domains of commuting and occupational PA. Multivariate logistic regression analysis showed lower level of leisure time PA, unemployment and being single independently predicting low level of PMH. No associations were found between any domains of PA and high level of PMH. The most common reasons for physical inactivity among men with a low level of PMH were lack of interest (28%) and unwillingness to practise sports alone (27%). CONCLUSIONS: The relationship between physical activity and positive mental health seems to vary between different domains of physical activity. The findings highlight the important role of leisure time physical activity, particularly in men with a low level of positive mental health. Strategies aimed at increasing physical activity for mental health benefits should focus particularly on providing opportunities for leisure time physical activity involving social interactions for men with lower mental wellbeing.